English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Are any of these solutions correct?

-5(6x - 1)^-7/6

7(6x - 1)^-5/6

7(6x - 1)^-13/6

-5(6x - 1)^-11/6

2007-01-27 02:45:59 · 6 answers · asked by Doug 2 in Science & Mathematics Mathematics

6 answers

f(x) = (6x-1)^7/6
f'(x) = (7/6)(6x-1)^1/6 * (6)
f'(x) = 7(6x-1)^1/6
f''(x) = (1/6)(7)(6x-1)^-5/6 *(6)
f''(x) = 7(6x-1)^-5/6

2007-01-27 02:53:32 · answer #1 · answered by seah 7 · 2 0

f(x) = (6x - 1)^(7/6)

To find the first derivative, we use the power rule and then the chain rule. Note that the derivative of the inside (6x - 1) is 6.

f'(x) = (7/6) (6x - 1)^(1/6) {6)

Simplifying this, the 6 will merge with the (7/6) into 7.

f'(x) = 7(6x - 1)^(1/6)

Now, we get the second derivative.

f''(x) = 7(1/6) (6x - 1)^(-5/6)

Merging the 7 and the 1/6, we get

f''(x) = (7/6) (6x - 1)^(-5/6)

2007-01-27 02:50:03 · answer #2 · answered by Puggy 7 · 1 0

the 2nd one, 7(6x - 1)^-5/6


the first deriv ends up being 7(6x-1)^1/6

so then the 2nd deriv is 7(6x - 1)^-5/6


*** on the answer above, he forgot the multiply by the deriv of the inside, which would be 6, so 7*(1/6)*6 is just 7

2007-01-27 02:50:25 · answer #3 · answered by kingsmansoysauce 2 · 2 0

f'(x) = (7 / 6) * 6 * (6x - 1) ^ (1 / 6) = 7 * (6x - 1) ^ (1 / 6)

f''(x) = (7 / 6) * 6 * (6x - 1) ^ (-5 / 6) = 7 * (6x - 1) ^ (-5 / 6)

Your second answer is right.

2007-01-27 02:54:49 · answer #4 · answered by Shashi 2 · 1 0

f(x) =(6x - 1)^7/6.

f ' (x) =(7/6) *(6x - 1) ^(1/6) *6
= 7 ( 6x - 1)^(1/6)

f'' (x) = 7 (1/6) (6x - 1) ^( - 5/6) * 6.

= 7(6x - 1) ^(- 5/6) Answer

2007-01-27 03:04:39 · answer #5 · answered by Anonymous · 0 0

f(x) = (6x - 1)^7/6

rule: du/dy (u)^a = a du (u)^(a-1)

f'(x) = 7/6 * 6(6x - 1)^(7/6 - 1)
f'(x) = 7(6x - 1)^(1/6)

f''(x) = 7*(1/6)*6(6x - 1)^(1/6-1)
f''(x) = 7 (6x- 1)^(-5/6)

so the second one is correct

2007-01-27 02:51:58 · answer #6 · answered by Anonymous · 1 0

fedest.com, questions and answers